Structural and near-IR photophysical studies on ternary lanthanide complexes containing poly(pyrazolyl)borate and 1,3-diketonate ligands. - Davies, G; Aarons, R; Motson, G; Jeffery, J; Adams, H; Faulkner, S; Ward, MD (2004)
The ligands tris[3-(2-pyridyl)pyrazol-1-yl]hydroborate (L1, potentially hexadentate) and bis[3-(2-pyridyl)pyrazol-1-yl]dihydroborate (L2, potentially tetradentate) have been used to prepare ternary lanthanide complexes in which the remaining ligands are dibenzoylmethane anions (dbm). [Eu(L1)(dbm)2] is eight-coordinate, with L1 acting only as a tetradentate chelate (with one potentially bidentate arm pendant) and two bidentate dbm ligands. [Nd(L1)(dbm)2] was also prepared but on recrystallization some of it rearranged to [Nd(L1)2][Nd(dbm)4], which contains a twelve-coordinate [Nd(L1)2]+ cation (two interleaved hexadentate podand ligands) and the eight-coordinate anion [Nd(dbm)4]- which, uniquely amongst eight-coordinate complexes having four diketonate ligands, has a square prismatic structure with near-perfect O8 cubic coordination. Formation of this sterically unfavourable geometry is assumed to arise from favourable packing with the pseudo-spherical cation. The isostructural series of complexes [Ln(L2)(dbm)2](Ln = Pr, Nd, Eu, Gd, Tb, Er, Yb) was also prepared and all members structurally characterised; again the metal ions are eight-coordinate, from one tetradentate ligand L2 and two bidentate dbm ligands. Photophysical studies on the complexes with Ln = Pr, Nd, Er, and Yb were carried out; all show the near-IR luminescence characteristic of these metal ions, with longer lifetimes in CD3OD than in CH3OH. For [Yb(L2)(dbm)2], two species with different luminescence lifetimes were observed in CH3OH solution, corresponding to species with zero or one coordinated solvent molecules, in slow exchange on the luminescence timescale. For [Nd(L2)(dbm)2] a single average solvation number of 0.7 was observed in MeOH. For [Pr(L2)(dbm)2] a range of emission lines in the visible and NIR regions was detected; time-resolved measurements show a particularly high susceptibility to quenching by solvent CH and OH oscillators.